RIAP PERTUMBUHAN JATI UNGGUL NUSANTARA DI KEBUN PERCOBAAN COGREG UNIVERSITAS NUSA BANGSA - Meiganati, Kustin Bintani; Rusli, Abdul Rahman (Universitas Nusa Bangsa, 2017)
The Cogreg Experimental Garden planted with fast growing teak has been cut down at the age of 5 years. After being cut down, the stump is maintained so that it grows trubusan. To see plant growth the dimensions of the tree need to be measured in the form of diameter and height of the tree. The data can also be used to measure how much plant growth occurs. The initial assumption of trubusan growth can be influenced by differences in the number of branches growing in the trubusan. Therefore the samples in the calculation of increment in this study were distinguished by the number of trubusan branches growing, namely: 1, 2 and 3 branches. The measurement results obtained data on trubusan growth as follows: 1 branch diameter = 2.915 cm / th, branch 2 = 2.625 cm / th and branch 3 = 2.785 cm / th. Height at branch 1 = 2.1975 m / th, branch 2 = 2.11 m / th and branch 3 = 2.215 m / th. Volume on branch 1 = 0.0275 m3 / th, branch 2 = 0.02 m3 / th and branch 3 = 0.025 m3 / th. From the data obtained, it will be seen the relationship between volume increment and the number of branches that grow on teak trubusan. Data is processed using a simple correlation test with a value of r = 0.159. This shows that there is a positive correlation between the number of trubusan branches and teak volume increments, but the correlation is very weak. This study concludes that the volume increment of JUN at the UNB Experimental Garden is not affected by the number of trubusan branches growing. This gives a recommendation that the trubusan branch that grows can be selected for a maximum of 3 branches.Â Key words: riap, volume, trubusan, branch, JUN